2012
DOI: 10.3109/00016357.2011.642002
|View full text |Cite
|
Sign up to set email alerts
|

The highly leukotoxic JP2 clone ofAggregatibacter actinomycetemcomitansin localized and generalized forms of aggressive periodontitis

Abstract: The presence of the JP2 clone of A. actinomycetemcomitans is strongly associated with both LAgP and GAgP in young adults in Morocco. This implies that treatment of AgP in this population should include microbiological screening and aim at eradication of the bacterium when present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 37 publications
1
31
3
Order By: Relevance
“…A decreased number of bacteria would reduce the likelihood of capturing the highly leukotoxic JP2 clone strains at the sampling occasions, although JP2 clone strains are still present in the oral cavity. An age predilection for JP2 clone infection of only the young appears, however, to be in contrast with more recent results obtained in Morocco (110). In the Moroccan study by Ennibi and coworkers, it was investigated if the JP2 clone was particularly linked to the localized forms versus the generalized forms of aggressive periodontitis (110).…”
Section: Acquisition Stability and Transmission Of The Jp2 Clone Ofcontrasting
confidence: 99%
See 1 more Smart Citation
“…A decreased number of bacteria would reduce the likelihood of capturing the highly leukotoxic JP2 clone strains at the sampling occasions, although JP2 clone strains are still present in the oral cavity. An age predilection for JP2 clone infection of only the young appears, however, to be in contrast with more recent results obtained in Morocco (110). In the Moroccan study by Ennibi and coworkers, it was investigated if the JP2 clone was particularly linked to the localized forms versus the generalized forms of aggressive periodontitis (110).…”
Section: Acquisition Stability and Transmission Of The Jp2 Clone Ofcontrasting
confidence: 99%
“…An age predilection for JP2 clone infection of only the young appears, however, to be in contrast with more recent results obtained in Morocco (110). In the Moroccan study by Ennibi and coworkers, it was investigated if the JP2 clone was particularly linked to the localized forms versus the generalized forms of aggressive periodontitis (110). Among Moroccan patients seeking periodontal treatment at the dental school in Rabat, Morocco, it was found that localized as well as generalized aggressive periodontitis patients were positive for the JP2 clone of A. actinomycetemcomitans (83% versus 69%, p =0.17) (110).…”
Section: Acquisition Stability and Transmission Of The Jp2 Clone Ofcontrasting
confidence: 99%
“…55 Interaction of S. tigurinus with A. actinomycetemcomitans might be of interest. 56 Since its recent identification, it is not clear whether modifying factors are associated with the presence of S. tigurinus in the human oral microbiome and if its detection in the oral cavity has direct clinical implications in systemic diseases.…”
Section: Association Of S Tigurinus With Oral Infectionsmentioning
confidence: 99%
“…Actually, we tested selected Moroccan essential oils (Origanum compactum, Thymus vulgaris and Cymbopogon martinii), which have never been studied on oral bacteria especially on the highly JP2 strain of Aa, a gram-negative facultative anaerobic bacterium and a well-known periopathogen strongly involved in aggressive periodontitis [1][2][3]. The choice of essential oils was based on their documented medicinal properties particularly antimicrobial effects and/or on their therapeutic use in traditional medicine in Moroccans (table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The oral species Aggregatibacter actinomycetemcomitans (Aa) is a period onto pathogen, known as strongly associated with aggressive periodontitis, severe periodontal diseases which lead to rapid destruction of supporting tissues of teeth in young adults [1][2][3]. Genome analysis revealed that this species comprises discrete clonal lineages represented by different serotypes (a, b, c, d, e, f) associated with periodontitis or health, which may help to explain their differences in virulence and in association with disease [4][5][6].…”
Section: Introductionmentioning
confidence: 99%